Regulation of Access to Higher Education in Brazil: Bibliometric Analysis of Literature (Global Journal of Human-Social Science, 2026)
The study sought to understand, through bibliographical research, how the debate in the scientific field regarding the regulation of access to higher education in Brazil between 1997 and 2017 was constituted. We mapped academic production based on the databases Web of Science, Scopus and Scielo, bibliometrically analyzing its impact, considering production and citation indicators. We point out the temporal distribution of articles and their impact and identify the journals most devoted to the topic.